AN ANALYSIS OF STUDENTS’ READING COMPREHENSION LEVEL AT NURUL FALAH SENIOR HIGH SCHOOL PEKANBARU - Viani, Anggun Octa; Roswati, Roswati (VISION, 2025)
This study examines the reading comprehension levels of students at Nurul Falah Senior High School Pekanbaru, focusing on three distinct categories: literal, inferential, and critical comprehension. A quantitative descriptive approach was employed, utilizing a reading comprehension test as the primary instrument. The population included 110 students, with a simple random sampling method selecting 20% for the study. The analysis revealed that the average literal comprehension score was 87.27, categorized as very good, indicating strong performance at this level. For inferential comprehension, the average score was 79.54, classified as good, demonstrating the students' ability to infer information effectively. However, the critical comprehension score averaged 53.75, falling into the less proficient category, highlighting a need for improvement in higher-order thinking skills. The findings underscore the necessity for targeted interventions to enhance critical reading abilities while sustaining strengths in literal and inferential comprehension. This research contributes to the broader discourse on literacy education, offering practical insights for educators and policymakers aiming to develop comprehensive reading skills in high school students.